Synthesis of alloyed Bi2TexSe(3-x) nanoparticles and thermoelectric characterization of bulk nanostructured materials obtained by their assembly. Issue 1804 (2015) - Bude, Romain; Divay, Laurent; Bisaro, Renato; Servet, Bernard; Leveugle, Elodie; Wyczisk, Frédéric; Carisetti, Dominique; Ziaei, Afshin; Galindo, Christophe
ABSTRACT: The optimization of the figure of merit of thermoelectric materials requires the simultaneous control of the material composition and microstructure. Assembly of nanoparticles obtained by a solution route is an attractive bulk fabrication method because size and shape of the nanoparticles can be tuned by variation of the synthesis conditions. Recently, new synthetic pathways were reported among which reducing agent assisted, surfactant free processes. We report here the evaluation of this method for the synthesis of Bi2 Tex Se3-x alloyed nanoparticles with varying selenium concentrations. X-ray diffraction studies conducted on powder and pellet samples show that two alloyed phases are present in the sample even at low selenium content. The careful study of the position of the diffraction peaks as function of the formulation shows that this behaviour could arise from the difference in reactivity of selenium and tellurium. Moreover, the electrical conductivity of the samples is shown to increase upon selenium addition while the Seebeck coefficient is reduced. Power factor shows an optimum value around 20% selenium content with a large tolerance in composition.